(untitled) (Research, Society and Development, 2021)
Textile and food effluents commonly contain in their composition dye compounds harmful to human health and the environment and in this context advanced oxidation technologies such as electrochemical processes have emerged as an alternative treatment for refractory compounds present in these wastewaters. Thus, this work investigated the degradation of the basic methylene blue dye at room temperature (25 ºC) via electrocatalytic treatment with commercial Ti/Ru0.3Ti0.7O2 anode (30% RuO2 and 70% of TiO2). Experimental studies at pH = 6.8 were performed to evaluate the effect of the electrolysis potential, nature and concentration of the electrolytic support and initial concentration of dye on the efficiency and kinetics of degradation. The results showed degradations greater than 90% in 60 min of treatment by indirect electrolysis using 0.01 mol L-1 NaCl and 0.01 mol L-1 Na2SO4 as electrolytic support under 5.0 V potential at concentrations between 5 mg L-1 and 25 mg L-1. Electrodegradation kinetics were typically first order. In general, the degradation efficiency values found confirmed the promising character of the application of dimensionally stable anodes in the depollution of colored wastewater.